Self excited induction generators driven by regulated wind or hydro turbine - Mohamed Faizal. (2009)
This report gives a very detailed explanation on the various steady-state performance characteristics of a 3-phase self-excited induction generator, which is driven at a constant speed by a regulated wind or hydro turbine. In the laboratory, the regulated turbine will be emulated by a synchronous motor. Induction motor on the other hand, can operate as a generator when it is driven by a prime mover with capacitor banks of appropriate sizes connected across its stator terminals. Such a machine is called Self Excited Induction Generator (SEIG). Load characteristics of the generator for various connections such as shunt, short-shunt and long-shunt connections will be evaluated and compared. Induction generators are very commonly used in isolated areas. The generator in this project is operating in self-excited mode due to the lack of electrical supply in remote areas. In this modern era, for isolated or remote areas, there is a serious need for renewable energy. Energy from natural resources such as sunlight, wind, rain, tides and geothermal heat are examples of renewable energy.